PENGUKURAN KINERJA KOPERASI BERBASIS BALANCED SCORECARD - Herawati, Novy Rachma; Isnandi, Alvian Viko; Sari, Yulia Eka (Universitas Kadiri, 2018)
Cooperative is a business entity consisting of a person or a legal entity cooperative with the basis of its activities based on the principle of Cooperatives as well as the people's economic movement based on the principle of kinship (Act of the Republic of Indonesia Number 25 Year 1992). Village Unit Cooperative serves as a service center for economic activities in rural areas and is an integral part of national development that has a significant role in the community economy. The purpose of this study is to know the performance of cooperatives in financial and nonfinancial in a balanced manner so it can be known the development of strategy achievement by using Balanced Scorecard based measurement, by displaying four Perspective namely Financial Perspective, Customer Perspective, Internal Business Process Perspective and Learning and Growth Perspective. The results obtained, financial and nonfinancial are still less balanced and the target is still not achieved. Generally Madurasa Village Unit Cooperative need innovation to make KUD more in trust people or society by providing requirement of member and must dare to compete with other business enitas because if not done then certainly will not compete so that achievement of target can be achieved.